The importance of occupational medicine in traffic accidents prevention - Jovanović, Jovica; Banić, Svetlana (Medical Word, 2020)
The aim of this study is the analysis of medical selection of drivers and candidates for car drivers sent to preliminary, periodic or special medical examination in the last ten years period. At the preliminary medical examination 2.3% of candidates were declared to be incapable, 8.2% of candidates had a limited driving ability. At the periodic medical examination 12.2% of drivers were declared to be incapable to driving and 28.7% of drivers had a limited driving ability. At the special medical examination 37.3% of drivers were declared to be incapable for driving and 53.9% of drivers had a limited driving ability. In our opinion, medical selection of drivers and candidates for car drivers is a significant preventive measure of traffic trauma.